2012
DOI: 10.1111/1574-6941.12002
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial diversity from the source to the tap: a comparative study based on 16S rRNA gene-DGGE and culture-dependent methods

Abstract: This study aimed to assess the influence of water treatment and distribution on the bacterial communities with particular emphasis on tap water. Samples from the water treatment plant, the bulk supply distribution system and household taps, supplied by the same drinking water treatment plant, were analyzed using culture-dependent and culture-independent methods. Water treatment imposed alterations in the composition of the bacterial community, although this effect was more evident in the cultivable bacteria ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
53
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(64 citation statements)
references
References 71 publications
(111 reference statements)
10
53
1
Order By: Relevance
“…Therefore, it is expected that in drinking water, both the diversity of bacterial species and the possible occurrence of antibiotic resistance will have different characteristics of what can be found in wastewater. Water disinfection is known to cause a dramatic bottleneck on bacterial diversity (Hoefel et al 2005;Eichler et al 2006;Vaz-Moreira et al 2013) and bacteria ubiquitous in aquatic environments, such as members of the genus Aeromonas, may be reduced to levels below the limit of detection by culture-dependent methods (Figueira et al 2011). However, other groups that comprise bacteria with recognized ubiquity and genome plasticity, demonstrated by the acquired capacity to degrade xenobiotics or to resist to some antibiotics, such as members of the genera Pseudomonas, Acinetobacter, or family Sphingomonadaceae, are commonly found in tap water (Vaz-Moreira et al 2014).…”
Section: Drinking Watermentioning
confidence: 99%
“…Therefore, it is expected that in drinking water, both the diversity of bacterial species and the possible occurrence of antibiotic resistance will have different characteristics of what can be found in wastewater. Water disinfection is known to cause a dramatic bottleneck on bacterial diversity (Hoefel et al 2005;Eichler et al 2006;Vaz-Moreira et al 2013) and bacteria ubiquitous in aquatic environments, such as members of the genus Aeromonas, may be reduced to levels below the limit of detection by culture-dependent methods (Figueira et al 2011). However, other groups that comprise bacteria with recognized ubiquity and genome plasticity, demonstrated by the acquired capacity to degrade xenobiotics or to resist to some antibiotics, such as members of the genera Pseudomonas, Acinetobacter, or family Sphingomonadaceae, are commonly found in tap water (Vaz-Moreira et al 2014).…”
Section: Drinking Watermentioning
confidence: 99%
“…Instead of the Kirby-Bauer antibiogram method, ATB panels (Antibiotic Susceptibility Testing Strips, bioMérieux) could be applied [16], nevertheless this tool also requires cultivable, oxidant microbial colony to be tested. Other studies revealed that in water supply systems the alterations in the composition of the bacterial community were higher among cultivable communities than 16S rRNA sequences [17], indicating that some part of biomass could be lost during the classical isolation procedure. That could lead to the omission of many ARB.…”
Section: Discussionmentioning
confidence: 97%
“…organic carbon), which is strongly limited • temperature conditions, which are not suitable for many bacterial species • occasionally inconvenient hydraulic conditions (i.a. water stagnation) • lack of light, lack of many competitive species These features make that water supply systems could be regarded as the niche, where only the minor part of whole plethora of microorganisms are able to survive, but still, the biodiversity of biofilm and planktonic forms of microorganisms occurring in pipes is wide, as it is shown in the numerous studies [15][16][17]. It is worth to mention that the guidelines for susceptibility testing are still subjected to changes and improvements, as new data are taken into account.…”
Section: Discussionmentioning
confidence: 99%
“…18,21 Despite these limitations, DGGE is strongly preferred and is considered one of the best techniques for monitoring the microbial community of foodstuffs in a comprehensive, rapid and reproducible manner. 5,9,[22][23][24][25] …”
Section: Why Pcr-dgge?mentioning
confidence: 99%